Patient’s best interest as viewed by nursing students - Zolkefli, Yusrita (Nursing ethics, 2024)
BackgroundIn recent years, patient advocacy has emerged as a prominent concept within healthcare. How nursing students decide what is best for their patients is not well understood.ObjectiveThe objective is to examine nursing students' views on doing what is best for patients during their clinical experiences and how they seek to establish patient interests when providing care. Research questions guiding the interview were as follows: (1) What are nursing students' perceptions of patient interests? (2) What factors influence nursing students' perceptions of advocating for patient’s interests?Research designQualitative descriptive research using thematic analysis.Participants and research contextData was collected through individual online interviews with nine nursing students with clinical experience.Ethical considerationsThe study was approved by the University Research Ethics Committee. Participants provided digital informed consent.ResultsThe students asserted that they are able to understand the patients' interests by placing emphasis on the patients' needs. They believe that it is crucial to adopt a collaborative strategy for the provision of care to meet these requirements. In addition, some of them expressed concern over the most effective methods of advocating for the interests of patients. Three themes were identified. (1) Focussing on patient needs first, (2) taking a collective approach, and (3) learning how to advocate.ConclusionsStudents understand and value the ethical commitments associated with advocating for the patient's best interest by considering factors such as prioritising the patient's needs, adopting a strategy that involves everyone, and acquiring the ability to undertake the advocacy role. Additionally, nursing education strategies in clinical contexts require additional study to inspire students to do what is in their patient’s best interests.